THU0590-HPR Self-Efficacy and Positive Adaptation in Patients with Polyarthritis. (10th June 2014) - Taal, E.; Bode, C.; Arends, R.; van de Laar, M.A.
Abstract : Background: A lack of self-efficacy, the confidence in one's own competencies to cope with the symptoms of arthritis, has been found to be related to negative aspects of psychological functioning such as feelings of depression and anxiety. There is an increasing attention for positive adaptation to chronic diseases, inspired by the upcoming field of positive psychology. The relationships between self-efficacy and positive adaptation in patients with polyarthritis has not been investigated. Objectives: To study the relationships of pain, fatigue, functional limitations and self-efficacy with indicators of positive adaptation to polyarthritis, namely purpose in life, positive affect and social and work participation. Methods: 331 patients (61% women, mean age=61 years, mean disease duration=14 years) participated in a questionnaire study. Positive adaptation was measured with PIL (purpose in life), PANAS (positive affect) and IPA (social and work adaptation). Self-efficacy to cope with pain and self-efficacy to cope with other symptoms of arthritis were measured with ASES. Pain was assessed with a VAS, fatigue with SF36 Vitality scale and functional limitations with HAQ-DI. Hierarchical multiple regression analyses were applied to analyse the relationships of physical health (pain, fatigue, functional limitations) and self-efficacy with positive adaptations. Results: In regression analyses physical health (pain, fatigue, functional limitations) significantly explained positive adaptation (R 2 : 0.15-0.50). Explained variance in positive adaptation significantly increased when Pain self-efficacy (ΔR 2 :0.03-0.06) or other symptoms self-efficacy (ΔR 2 : 0.07-0.18). In most analyses pain and other symptoms self-efficacy pain and other symptoms self-efficacy were stronger predictors of positive adaptation than pain, fatigue or functional limitations. Except for one model (purpose in life, other symptoms self-efficacy) self-efficacy was found to be partly mediating the relationship between physical health (pain, fatigue, functional limitations) and positive adaptation. Conclusions: This study showed that self-efficacy is significantly related to positive adaptation in polyarthritis. A longitudinal study should be done to get more insight in the causality of the relations. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.6008